Review on modeling theories of electrosensitive hydrogels for cartilage tissue engineering - Farooqi, Abdul Razzaq; Seitz, Hermann; van Rienen, Ursula (Frontiers in Bioengineering and Biotechnology, 2025)
Electrosensitive hydrogels are smart biomaterials that swell, shrink, deform, and bend when an external electric field is applied. These hydrogels have enormous potential for the controlled therapeutic delivery of biochemical substances to the affected area, thus promoting tissue regeneration. Computational modeling and simulation approaches have provided researchers with cost-effective predictive models that can be used to optimize in vitro and in vivo experimental protocols. In this article, we present a review of the modeling theories that can be used for the modeling and numerical simulation of electrosensitive hydrogels immersed in a solution with an applied electric field for cartilage tissue engineering. Each theory presents tradeoffs for the numerical modeling of cartilage repair implants. The selection of an appropriate theory depends on the required accuracy, time-dependent application, and deformation behavior. Although most simulations are limited to one-dimensional cases, multidimensional simulations are crucial. By reviewing the modeling theories of electrosensitive hydrogels, this article aims to inspire researchers to model the electrical stimulation of electrosensitive hydrogels for various applications, including cartilage tissue engineering.